Correlation between HbA1c Levels and Red Distribution Cell Width in Type 2 Diabetes Mellitus Patients - Rahma, Hadiyatur; Siregar, Jelita; Syafril, Santi; Ganie, Ratna Akbari; Siregar, Dewi Indah Sari; Ginting, Almaycano (Indonesian Journal of Medicine, 2024)
Background: HbA1c is used as a parameter for diagnosis and monitoring of diabetes mellitus (DM). Apart from that, HbA1c, red blood cells also experience changes which result in changes in erythrocyte structure and hemodynamic characteristics. The parameter that changes in this case is red cell distribution width (RDW). This study aimed to analyze correlation between HbA1c levels and RDW in type 2 DM patients. Subjects and Method: This a cross sectional study conducted at H. Adam Malik General Central Hospital, Medan, North Sumatera, Indonesia, from December 2022-April 2023. Total sample of 75 type 2 DM patients was selected consecutively. The dependent variable was RDW. The independent variable was HbA1c. Data of RDW and HbA1c were collected from complete blood count test. Data were analyzed using the Spearman correlation. Results: HbA1c was negatively associated with RDW, but it was statistically non-significant (r= -0.08; p= 0.508). Conclusion: HbA1c is negatively associated with RDW, but it is statistically non-significant.   Keywords: diabetes melitus, HbA1c, red cell distribution width